Alkaline electrolysis water electrode with three metal sites cooperatively regulated and controlled as well as preparation method and application of alkaline electrolysis water electrode
By using in-situ growth method in alkaline electrolytic water electrodes, the problems of low electrode activity and poor stability are solved, and efficient and stable hydrogen production performance of electrolytic water is achieved.
Patent Information
- Application Number
- CN202510215464.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-26
AI Technical Summary
It is difficult for existing alkaline electrolytic water electrodes to achieve a good balance between reaction activity and stability, resulting in low efficiency and poor stability during the electrolytic water process.
Sm and Ce doped RuO2 catalyst electrodes were prepared by in-situ growth. The catalytic activity and stability of the electrodes were coordinated under specific preparation methods and doping ratio conditions using Ce's multivalent electronic structure and Sm's unique magnetic structure.
It achieves a current density of 830mA/cm2 and 1500mA/cm2 at 1.8V and 2.0V voltages, respectively, and operates stably for more than 500h at a current density of 1000mA/cm2, which significantly improves the hydrogen production performance and stability of the electrode.
Smart Images

Figure CN119859816A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of hydrogen production by water electrolysis, and specifically relates to an alkaline water electrolysis electrode with coordinated regulation of three metal sites, and a preparation method and application thereof. Background Art
[0002] In recent years, with the increasing energy crisis and environmental problems, the demand for global sustainable development has become more urgent. In this context, the development of clean and renewable energy is considered to be a key way to meet these challenges. Hydrogen has become an ideal energy carrier due to its high energy density, zero carbon emissions and renewability, and has become one of the current research hotspots. Hydrogen production by electrolysis of water driven by renewable energy is a green and environmentally friendly technology for preparing high-purity hydrogen. It can not only avoid the consumption of fossil fuels, but also make full use of abundant electrical energy. It is of great significance to promote global energy transformation and achieve sustainable development. At present, according to the environment of the electrolyte, electrolyzed water can be divided into alkaline electrolyzed water and acidic electrolyzed water. Alkaline electrolyzed water has a relatively better application prospect because it does not contain precious metals, has low cost and high degree of commercialization.
[0003] The electrode reaction in the process of water electrolysis can be divided into oxygen evolution reaction at the anode end and hydrogen evolution reaction at the cathode end. The oxygen evolution reaction at the anode end is a four-electron transfer process, which requires a large free energy and has complicated steps. It is the rate-determining step in the process of water electrolysis. Therefore, in order to achieve efficient and long-term operation of alkaline water electrolysis, it is necessary to develop a highly active and stable anode electrode.
[0004] Currently, the most commonly used nickel electrode and Raney nickel electrode in alkaline water electrolysis cannot achieve a good balance between reactivity and stability, and it is difficult to meet people's current needs. Transition metals and rare earth elements have a unique electron orbital structure and electronic structure diversity, so transition metal and rare earth element oxides are considered to be potential alkaline water electrolysis electrode materials. However, traditional metal oxides or single metal doped oxides are difficult to have both high activity and high stability in practical applications.
[0005] CN117107252A discloses a rare earth Ce-doped RuO2 catalyst and its preparation method and application. The RuO2 catalyst is a hollow sphere structure, and the rare earth Ce is doped on the surface of the hollow sphere; Ce induces the rearrangement of the charge on the Ru surface, and enhances the adsorption capacity of the electrode surface to the intermediate (*OH, *OOH) to enhance the catalytic ability. It is known that the increase in the valence state of Ru causes the d-band center to be close to the Fermi level, thereby improving the interaction ability between Ru and oxygen-containing intermediates. However, Ru-based catalysts usually have insufficient stability as water electrolysis electrodes, mainly due to the peroxidation dissolution of Ru. Although the high valence state of Ru is conducive to improving performance, it is not conducive to electrode stability.
[0006] In the prior art, the technology of Sm doping Ru-based catalysts has not been reported. The preparation of catalysts formed by doping with more than one metal oxide is to make different metals doped to synergistically improve the catalytic activity and stability under certain preparation process conditions. Summary of the invention
[0007] In order to overcome this problem, the purpose of the present invention is to provide an alkaline water electrolysis electrode with coordinated regulation of three metal sites and its preparation method and application. The present invention prepares a RuO2 catalyst electrode doped with Sm and Ce in situ grown on the electrode surface by an in-situ growth method. Based on the variable valence electron structure of Ce and the unique magnetic structure of Sm, under specific preparation methods and doping ratio conditions, Ce doping has a certain electronic regulation effect on the active Ru site in the electrode (making Ru gain electrons and reduce the valence state), improves the catalytic activity of the electrode, and is beneficial to the stability of the electrode; and under specific preparation methods and doping ratio conditions, Sm doping has a certain strain regulation effect on the active Ru site in the electrode (shortening the Ru-O bond length), thereby improving the reaction stability of the electrode. The coordinated regulation of the three metal sites effectively solves the problems of low activity and poor stability of the electrode in the prior art.
[0008] In order to achieve the above object, the present invention adopts the following scheme:
[0009] A method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites comprises the following steps:
[0010] (1) oxidizing lignin sulfonate in a solution to obtain an oxidized lignin sulfonate solution;
[0011] (2) adding ammonia water to the oxidized lignin sulfonate solution to adjust the pH, and then adding metal salts in proportion, the metals including Ru, Ce, and Sm, and mixing them well to carry out a hydrothermal reaction with the substrate carrier, the hydrothermal reaction temperature is 80 to 120° C., and the time is 3 to 10 hours to obtain an electrode precursor;
[0012] (3) Calcinate the electrode precursor obtained in (2) at a temperature of 200 to 600° C. for 1 to 8 h to obtain an alkaline water electrolysis electrode with coordinated regulation of three metal sites.
[0013] In the present invention, metal ions react with lignin sulfonate to form complexes, which are adsorbed onto the substrate carrier through hydroxyl groups, sulfonic acid groups, etc. Finally, after calcination, the metals are connected through oxygen elements.
[0014] Preferably, in step (1), lignin sulfonate is added to a solution (i.e., a mixture of water and ethanol, ethanol refers to anhydrous ethanol), ultrasonically dispersed and mixed, and a small amount of hydrogen peroxide is added to oxidize the lignin sulfonate to obtain an oxidized lignin sulfonate solution. By oxidizing the lignin sulfonate, the metal complexing ability of the lignin sulfonate is improved;
[0015] Preferably, in step (1), the ratio of the added lignin sulfonate to hydrogen peroxide is 8-16 mmol:0.1-1 mL; the volume ratio of water to ethanol is (1-9):1; and the ultrasonic dispersion time is 1-10 min.
[0016] In step (2), ammonia water is added to the oxidized lignin sulfonate solution obtained in (1) to adjust the pH to a weak alkaline state. This environment is conducive to the complexation of lignin sulfonate with metal ions. Metal salts RuCl3, Ce(NO3)3, and Sm(NO3)3 are added in proportion in sequence. After ultrasonic dispersion, they are placed in a hydrothermal kettle together with the substrate carrier. After the hydrothermal reaction, the electrode surface is rinsed with deionized water to obtain an electrode precursor. Ru salt is added first, so that the main components are in the interior and the metal elements responsible for regulation are distributed in the surface layer, which can better contact the reaction interface and improve the utilization rate of the doping elements.
[0017] Preferably, the volume ratio of the ammonia water added in step (2) to the hydrogen peroxide solution added in step (1) is 0.1-1.5:0.1-1; and the metal salt is RuCl3, Ce(NO3)3, or Sm(NO3)3.
[0018] Preferably, in step (2), the molar ratio of the added RuCl3, Ce(NO3)3, and Sm(NO3)3 is (6.9-7.1):(1.9-2.1):(0.9-1.1).
[0019] In step (2), mixing is performed by ultrasonic dispersion, and the ultrasonic dispersion time is 1 to 5 hours.
[0020] In step (2), the substrate carrier is one of nickel foam, nickel mesh, and carbon paper.
[0021] In step (3), the electrode precursor obtained in (2) is placed in a muffle furnace for calcination to further oxidize the metal ions on the electrode surface and to make the metal oxides adsorbed on the surface more tightly bonded to the substrate carrier. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After drying, a highly active and stable alkaline water electrolysis electrode with coordinated regulation of the three metal sites is obtained.
[0022] Preferably, in step (3), the calcination temperature is 300-500°C.
[0023] Preferably, in step (3), the drying method is at least one of ordinary drying, vacuum drying and freeze drying.
[0024] Another object of the present invention is to provide an alkaline water electrolysis electrode with coordinated regulation of three metal sites prepared by the aforementioned preparation method.
[0025] Another object of the present invention is to disclose the application of an alkaline water electrolysis electrode with coordinated regulation of three metal sites in hydrogen production by water electrolysis (especially hydrogen production by alkaline water electrolysis). Specifically, hydrogen production by alkaline water electrolysis is carried out in an electrolyzer device. The electrolyzer device includes an electrolyzer fixture, a peristaltic pump, an alkali liquid tank and a temperature control device.
[0026] Preferably, the diaphragm used in the electrolytic cell is Zirfon PERL UTP 500 alkaline water electrolysis composite diaphragm.
[0027] Preferably, the flow rate of the electrolyte is 0 to 100 mL / min.
[0028] Preferably, the electrolyte temperature during the electrolysis reaction is 60 to 80°C.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1) The present invention provides an alkaline water electrolysis electrode with coordinated regulation of three metal sites, and the required metal oxide catalyst is precipitated on a substrate carrier by a hydrothermal method; compared with traditional coating, the in-situ growth method combines the substrate with the high-activity components on the surface more tightly, avoiding the phenomenon of catalyst shedding during use.
[0031] 2) Compared with other polyhydroxy complexing agents, the lignin sulfonate used in the present invention contains not only abundant hydroxyl groups but also sulfonic acid groups. These groups are conducive to better complexing reaction between lignin sulfonate and metal ions in aqueous solution. Moreover, after oxidation treatment, the lignin sulfonate can further improve the complexing ability of metal ions, thereby further improving the catalytic performance.
[0032] 3) The Sm and Ce doped RuO2 catalyst electrode provided by the present invention, based on the variable valence electron structure of Ce and the unique magnetic structure of Sm, under the specific preparation method and doping ratio conditions, the Ce doping has a certain electronic regulation effect on the active Ru sites in the electrode (making Ru gain electrons and reduce the valence state), improves the catalytic activity of the electrode, and is beneficial to the stability of the electrode; and under the specific preparation method and doping ratio conditions, the Sm doping has a certain strain regulation effect on the active Ru sites in the electrode (shortening the Ru-O bond length), thereby improving the reaction stability of the electrode. Therefore, in the application of alkaline water electrolysis, the electrode can reach 830mA / cm at 1.8V and 2.0V voltages respectively.2 and 1500mA / cm 2 The current density is 1000mA / cm 2 It can operate stably for more than 500 hours at a current density of , and has good hydrogen production performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only show schematic diagrams of certain embodiments of the present invention, and therefore should not be regarded as limiting the scope. For ordinary technical personnel in this field, other related drawings can be obtained based on these drawings under the premise of continuous creative work.
[0034] Figure 1 is a scanning electron microscope image of the electrode described in Example 2 of the present invention;
[0035] Figure 2 X-ray photoelectron spectra of active Ru sites of the electrode described in Example 2 of the present invention and different electrodes of Comparative Examples 1, 2 and 3;
[0036] Figure 3 XANES spectra of the electrode described in Example 2 and different electrodes of Comparative Example 1, Comparative Example 2 and Comparative Example 3;
[0037] Figure 4 The electrochemical performance of the electrode described in Example 2 of the present invention is compared with that of different electrodes in Comparative Example 1, Comparative Example 2, and Comparative Example 3;
[0038] Figure 5 The electrode described in Example 2 of the present invention is in 30% KOH, 1000mA / cm 2 Stability test results under current density. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0040] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from the market or synthesized from raw materials purchased from the market.
[0041] The present invention discloses a method for preparing a highly active and stable alkaline water electrolysis electrode synergistically regulated by three metal sites, comprising the following steps:
[0042] (1) Add lignin sulfonate to a mixture of water and ethanol, add a small amount of hydrogen peroxide by ultrasonic dispersion, oxidize the lignin sulfonate, and enhance the complexing ability of the lignin sulfonate to metals.
[0043] Specifically, the added lignin sulfonate is 8 to 16 mmol.
[0044] Specifically, the volume ratio of water to ethanol is: (1-9):1.
[0045] Specifically, the ultrasonic time is 1 to 10 minutes.
[0046] Specifically, the volume of the added hydrogen peroxide is 0.1-1 mL.
[0047] (2) Then, ammonia water is added to the solution obtained in (1) to adjust the pH to a weak alkaline state (e.g., 7 to 9). This environment is conducive to the complexation between lignin sulfonate and metal ions. Metal salts are added in proportion in sequence, and after ultrasonic dispersion, they are placed in a hydrothermal kettle together with the substrate carrier. After the hydrothermal reaction, the electrode (i.e., the substrate carrier loaded with metal salts, the electrode state at this time is the metal ion complex state connected to the substrate by organic acid, and the water washing removes the unreacted metal ions and organic acid. The state of the complex is not enough to achieve a relatively ideal electrolytic performance, and further calcination is required to generate oxides) surface is rinsed with deionized water to obtain an electrode precursor.
[0048] Specifically, the volume of the added ammonia water is 0.1 to 1.5 mL.
[0049] Specifically, the metal salt is RuCl3, Ce(NO3)3, or Sm(NO3)3.
[0050] Specifically, the added metal elements and their ratios are: (6.9-7.1):(1.9-2.1):(0.9-1.1).
[0051] Specifically, the ultrasonic dispersion time is 1 to 5 hours.
[0052] Specifically, the substrate carrier is one of nickel foam, nickel mesh, and carbon paper.
[0053] Specifically, the hydrothermal reaction temperature is 80-120° C. and the time is 3-10 hours.
[0054] (3) The precursor obtained in (2) is placed in a muffle furnace and calcined to further oxidize the metal ions on the electrode surface and to make the metal oxides adsorbed on the surface more tightly bonded to the base carrier. The electrode sheet (i.e., the base carrier loaded with metal oxides) is then taken out and rinsed with deionized water to remove unstable components on the surface (i.e., unreacted metal ions and organic acids). After drying, a highly active and stable alkaline water electrolysis electrode with coordinated regulation of the three metal sites is obtained.
[0055] Specifically, the calcination temperature is 200-600° C. and the calcination time is 1-8 hours.
[0056] Specifically, the drying method is at least one of ordinary drying, vacuum drying, and freeze drying.
[0057] The present invention will be further described below through specific embodiments.
[0058] Example 1
[0059] A method for preparing a highly active and stable alkaline water electrolysis electrode synergistically regulated by three metal sites comprises the following steps:
[0060] (1) 8 mmol of sodium lignin sulfonate (purchased from Merck, the same below) was added to a mixture of 50 mL of water and 50 mL of ethanol, and ultrasonically dispersed for 2 min. 0.2 mL of hydrogen peroxide was added and ultrasonically dispersed for 5 min (during this process, dissolution, mixing and oxidation were performed).
[0061] (2) 0.2 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3, Ce(NO3)3, and Sm(NO3)3 were added in sequence, wherein the mass of RuCl3 was 1.452 g, and the molar ratio of RuCl3, Ce(NO3)3, and Sm(NO3)3 was 7:1.9:0.9. Ultrasonic dispersion was performed for 2 h, and the solution was placed in a hydrothermal autoclave at 120° C. together with a cut nickel mesh (Φ=3 cm), reacted for 5 h, and rinsed with deionized water after hydrothermal treatment to obtain the electrode precursor.
[0062] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 300° C. for 5 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the nickel mesh. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After freeze-drying, the alkaline water electrolysis electrode is obtained.
[0063] Example 2
[0064] A method for preparing a highly active and stable alkaline water electrolysis electrode synergistically regulated by three metal sites comprises the following steps:
[0065] (1) Add 10 mmol of sodium lignin sulfonate to a mixture of 70 mL of water and 30 mL of ethanol, and disperse by ultrasonication for 4 min. Add 0.2 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0066] (2) 0.4 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3, Ce(NO3)3, and Sm(NO3)3 were added in sequence, wherein the mass of RuCl3 was 1.452 g, and the molar ratio of RuCl3, Ce(NO3)3, and Sm(NO3)3 was 7:2:1. Ultrasonic dispersion was performed for 2 h, and the solution was placed in a hydrothermal autoclave together with a cut nickel mesh (Φ=3 cm) at 100°C for reaction for 5 h. After hydrothermal treatment, the solution was rinsed with deionized water to obtain the electrode precursor.
[0067] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 400° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the nickel mesh. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After freeze-drying, the alkaline water electrolysis electrode is obtained.
[0068] Example 3
[0069] A method for preparing a highly active and stable alkaline water electrolysis electrode synergistically regulated by three metal sites comprises the following steps:
[0070] (1) Add 12 mmol of sodium lignin sulfonate to a mixture of 60 mL of water and 40 mL of ethanol, and disperse by ultrasonication for 6 min. Add 0.6 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0071] (2) 0.8 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3, Ce(NO3)3, and Sm(NO3)3 were added in sequence, wherein the mass of RuCl3 was 1.452 g, and the molar ratio of RuCl3, Ce(NO3)3, and Sm(NO3)3 was 7.1:2:1.1. Ultrasonic dispersion was performed for 2 h, and the solution was placed in a hydrothermal autoclave at 90°C together with a cut nickel mesh (Φ=3 cm) and reacted for 5 h. After hydrothermal treatment, the solution was rinsed with deionized water to obtain the electrode precursor.
[0072] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 500° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the nickel mesh. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After freeze-drying, the alkaline water electrolysis electrode is obtained.
[0073] Comparative Example 1
[0074] A method for preparing an alkaline water electrolysis electrode regulated by a single metal site comprises the following steps:
[0075] (1) Add 10 mmol of sodium lignin sulfonate to a mixture of 70 mL of water and 30 mL of ethanol, and disperse by ultrasonication for 4 min. Add 0.2 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0076] (2) 0.4 mL of ammonia water was added to the solution obtained in (1) to adjust the pH, and then 1.452 g of RuCl3 was added and ultrasonically dispersed for 2 h. The solution was placed in a hydrothermal reactor together with a cut nickel mesh (Φ=3 cm) at 100° C. and reacted for 5 h. After hydrothermal treatment, the solution was rinsed with deionized water to obtain the electrode precursor.
[0077] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 400° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the nickel mesh. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After freeze-drying, the alkaline water electrolysis electrode is obtained.
[0078] Comparative Example 2
[0079] A method for preparing a highly active and stable alkaline water electrolysis electrode regulated by a bimetallic site, comprising the following steps:
[0080] (1) Add 10 mmol of sodium lignin sulfonate to a mixture of 70 mL of water and 30 mL of ethanol, and disperse by ultrasonication for 4 min. Add 0.2 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0081] (2) 0.4 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3 and Sm(NO3)3 were added in sequence, wherein the mass of RuCl3 was 1.452 g and the molar ratio of RuCl3 to Sm(NO3)3 was 7:1. Ultrasonic dispersion was performed for 2 h, and the solution was placed in a hydrothermal autoclave together with a cut nickel mesh (Φ=3 cm) at 100°C for reaction for 5 h. After hydrothermal treatment, the solution was rinsed with deionized water to obtain the electrode precursor.
[0082] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 400° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the nickel mesh. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After freeze-drying, the alkaline water electrolysis electrode is obtained.
[0083] Comparative Example 3
[0084] A method for preparing a highly active and stable alkaline water electrolysis electrode regulated by a bimetallic site, comprising the following steps:
[0085] (1) Add 10 mmol of sodium lignin sulfonate to a mixture of 70 mL of water and 30 mL of ethanol, and disperse by ultrasonication for 4 min. Add 0.2 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0086] (2) 0.4 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3 and Ce(NO3)3 were added in sequence, wherein the mass of RuCl3 was 1.452 g and the molar ratio of RuCl3 to Ce(NO3)3 was 7:2. Ultrasonic dispersion was performed for 2 h, and the solution was placed in a hydrothermal autoclave together with a cut nickel mesh (Φ=3 cm) at 100°C for reaction for 5 h. After hydrothermal treatment, the solution was rinsed with deionized water to obtain the electrode precursor.
[0087] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 400° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the nickel mesh. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After freeze-drying, the alkaline water electrolysis electrode is obtained.
[0088] Comparative Example 4
[0089] A method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites comprises the following steps:
[0090] (1) Add 10 mmol of sodium lignin sulfonate to a mixture of 70 mL of water and 30 mL of ethanol, and disperse by ultrasonication for 4 min. Add 0.2 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0091] (2) 0.4 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3, Ce(NO3)3, and Cr(NO3)2 were added in sequence, wherein the mass of RuCl3 was 1.452 g, and the molar ratio of RuCl3, Ce(NO3)3, and Cr(NO3)2 was 7:2:1. Ultrasonic dispersion was performed for 2 h, and the solution was placed in a hydrothermal autoclave together with a cut nickel mesh (Φ=3 cm) at 100°C for reaction for 5 h. After the hydrothermal reaction, the solution was rinsed with deionized water to obtain the electrode precursor.
[0092] (3) The electrode precursor obtained after the hydrothermal reaction is placed in a muffle furnace and calcined at 400° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly combined with the nickel foam. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After drying, the alkaline water electrolysis electrode is obtained.
[0093] Comparative Example 5
[0094] A method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites comprises the following steps:
[0095] (1) Add 10 mmol of sodium lignin sulfonate to a mixture of 70 mL of water and 30 mL of ethanol, and disperse by ultrasonication for 4 min. Add 0.2 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0096] (2) 0.4 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3, Mn(NO3)2, and Cr(NO3)2 were added in sequence, wherein the mass of RuCl3 was 1.452 g, and the molar ratio of RuCl3, Mn(NO3)2, and Cr(NO3)2 was 7:2:1. Ultrasonic dispersion was performed for 2 h, and the solution was placed in a hydrothermal autoclave together with a cut nickel mesh (Φ=3 cm) at 100°C for reaction for 5 h. After hydrothermal treatment, the solution was rinsed with deionized water to obtain the electrode precursor.
[0097] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 400° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the carbon paper. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After vacuum drying, the alkaline water electrolysis electrode is obtained.
[0098] Comparative Example 6
[0099] A method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites comprises the following steps:
[0100] (1) Add 10 mmol of sodium lignin sulfonate to a mixture of 70 mL of water and 30 mL of ethanol, and disperse by ultrasonication for 4 min. Add 0.2 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0101] (2) 0.4 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3, Mn(NO3)2, and La(NO3)2 were added in sequence, wherein the mass of RuCl3 was 1.452 g, and the molar ratio of RuCl3, Mn(NO3)2, and La(NO3)2 was 7:2:1. Ultrasonic dispersion was performed for 2 h, and the solution was placed in a hydrothermal autoclave together with a cut nickel mesh (Φ=3 cm) at 100°C for reaction for 5 h. After hydrothermal treatment, the solution was rinsed with deionized water to obtain the electrode precursor.
[0102] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 400° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the carbon paper. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After vacuum drying, the alkaline water electrolysis electrode is obtained.
[0103] Comparative Example 7
[0104] A method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites comprises the following steps:
[0105] (1) Add 10 mmol of sodium lignin sulfonate to a mixture of 70 mL of water and 30 mL of ethanol, and disperse by ultrasonication for 4 min. Add 0.2 mL of hydrogen peroxide, and disperse by ultrasonication for 5 min.
[0106] (2) 0.4 mL of ammonia water was added to the solution obtained in (1) to adjust the pH value, and then RuCl3, Cr(NO3)2, and Sm(NO3)3 were added in sequence, wherein the mass of RuCl3 was 1.452 g, and the molar ratio of RuCl3, Cr(NO3)2, and Sm(NO3)3 was 7:2:1. The mixture was ultrasonically dispersed for 5 h, and placed in a hydrothermal autoclave at 110° C. together with a cut nickel mesh (Φ=3 cm), reacted for 6 h, and rinsed with deionized water after hydrothermal treatment to obtain the electrode precursor.
[0107] (3) The precursor obtained after hydrothermal treatment is placed in a muffle furnace and calcined at 400° C. for 4 hours to further oxidize the metal ions that have not reacted completely and to make the metal oxides adsorbed on the surface more tightly bonded to the carbon paper. The electrode sheet is then taken out and rinsed with deionized water to remove unstable components on the surface. After vacuum drying, the alkaline water electrolysis electrode is obtained.
[0108] Comparative Example 8
[0109] Compared with Example 2, the mass of RuCl3 remains unchanged, and RuCl 3、 The molar ratios of Ce(NO3)3 and Sm(NO3)3 were adjusted to 7:2:2, 7:2:0.5, 7:1:1, and 7:3:1, respectively.
[0110] Comparative Example 9
[0111] Compared with Example 2, the step of "adding 0.2 mL of hydrogen peroxide and ultrasonically dispersing for 5 minutes" was omitted.
[0112] Application Example 1
[0113] The application of a highly active and stable alkaline water electrolysis electrode with coordinated regulation of three metal sites in hydrogen production by water electrolysis comprises the following steps:
[0114] The cleaned electrode sheet and the finished diaphragm are installed in the electrolytic cell fixture in sequence, and then connected to the test system, including: peristaltic pump, alkali liquid tank, temperature control system and electrochemical test platform. The anode is the alkaline water electrolysis electrode prepared in the embodiment or comparative example, and the cathode is the commercially available nickel mesh electrode. The electrolysis temperature is set to 80°C. After the system temperature stabilizes at 80°C, the test is started at 500mA / cm 2The electrodes and diaphragms in the electrolyzer are activated with a current density of 1000 mA / cm2 until the performance becomes stable. The activation is completed and the required hydrogen production performance test is continued. First, the polarization curve test is performed on the activated electrolyzer to compare the performance of the embodiment and the comparative example at the same voltage. Then, the activation is completed with a constant current (1000 mA / cm2). 2 ) polarization to evaluate the stability of the electrode. In order to further ensure the stability of the pH inside the electrolytic cell during the reaction, the alkali solution in the alkali solution tank was replaced after every 150 hours of reaction.
[0115] Table 1 shows the examples and comparative examples. In Application Example 1, 500 mA / cm 2 The charge transfer resistance was measured at a current density of 500 mA / cm 2 Overpotential test results under current density. The resistance and overpotential were tested by an electrochemical workstation, and the implementation standards were GB / T 38894-2020 and GB / T45092-2024 respectively.
[0116] Table 1 Electrochemical performance test results
[0117] Charge transfer resistance(Ω) <![CDATA[500mA / cm 2 Overpotential(mV)]]> Example 1 1.75 442 Example 2 1.63 430 Example 3 1.79 439 Comparative Example 1 8.47 723 Comparative Example 2 5.96 688 Comparative Example 3 4.34 562 Comparative Example 4 3.78 516 Comparative Example 5 4.15 551 Comparative Example 6 3.21 503 Comparative Example 7 10.78 975 Comparative Example 8 (7:2:2) 2.83 474 Comparative Example 8 (7:2:0.5) 2.97 487 Comparative Example 8 (7:1:1) 3.56 509 Comparative Example 8 (7:3:1) 2.57 451 Comparative Example 9 4.76 591
[0118] As can be seen from Table 1, the synergistic catalytic effect of the three metals Ru, Ce, and Sm in the alkaline water electrolysis electrode is better than other metal combinations (Ru / Ce / Cr, Ru / Mn / Cr, Ru / Mn / La, Ru / Sm / Cr). Comparative Examples 4-7 also use three metal sites, some of the metals are different from the examples, and the charge transfer resistance and overpotential performance data are not as good as the examples.
[0119] Figure 1 The SEM of the catalyst generated on the electrode surface described in Example 2 shows that metal oxide nanoparticles have grown on the surface of the original nickel mesh substrate. This in-situ growth method can effectively avoid the catalyst shedding phenomenon caused by traditional coating methods, and the metal oxide nanoparticles on the surface can provide a larger active specific surface area, thereby enhancing the electrochemical activity of the electrode.
[0120] Figure 2 is the X-ray photoelectron spectrum of the electrode Ru of Example 2 and the comparative example, + Representation 4 + The peak produced by valence state Ru; 0 represents the peak produced by 0 valence state Ru; sat. is the satellite peak; Ru 3d, 3d 3 / 2 and 3D 5 / 2 Refers to the outermost 3d orbital of Ru, which can be split into 3d 3 / 2 and 3D 5 / 2 , C 1sIt is the 1s orbital of carbon. By comparing Example 2 with Comparative Example 2, it can be seen that in the electrode prepared by the preparation method of the present invention, the doping of Ce causes a negative shift in the binding energy of the active Ru site in the electrode, which means that the electronic valence state of Ru decreases to a certain extent (representing the electron gain of the Ru site). The decrease in valence can accelerate the reaction rate of the intermediates in the electrolysis of water, thereby accelerating the overall reaction kinetics and improving the catalytic ability of the electrode. Specifically, the electron gain of the Ru site can promote the reaction kinetics of water decomposition to generate intermediates, and the low-valence Ru can also avoid the overoxidation of Ru and maintain the stability of the electrode.
[0121] Figure 3 The normalized XANES spectra of Example 2 and the comparative example electrode are shown in Table 2. By comparing Example 2 and Comparative Example 3, it can be seen that due to the doping of Sm, the Ru-O bond length in the electrode will be shortened to a certain extent (shortened by about 1.5 ), the shortening of the bond length can maintain the stability of the Ru-O bond during the reaction, avoid bond breaking and deactivation, and show excellent stability of the electrode. The difficulty of shortening the Ru-O bond length is to accurately control the structure of the catalyst, especially the local atomic arrangement, which is closely related to the metal molar ratio and preparation method of the present invention.
[0122] Figure 3 The horizontal axis R represents the bond length; the vertical axis represents the absorption coefficient, which means the intensity or represents the strength of the bond. Ru K-edge represents the characteristic X-ray absorption edge of Ru, reflecting the relationship between the energy of the X-ray and the binding energy of the K electron shell of the target atom.
[0123] Figure 4 The polarization curves of the electrodes described in Example 2 and the comparative example are compared. It can be seen that, compared with the comparative example, at the same voltage, the electrode described in Example 2 generates a larger current density, which means that its hydrogen production efficiency is higher and the energy consumption is lower in actual production. Among them, the electrode described in Example 2 can reach 830mA / cm at a voltage of 1.8V and 2.0V respectively. 2 , 1500mA / cm 2 The current density is better than that of the electrodes described in Comparative Examples 1, 2, and 3. Specifically, Comparative Example 1: 1.8 V (278 mA / cm 2 ), 2.0V(627mA / cm 2 ); Comparative Example 2: 1.8V (312mA / cm 2 ), 2.0V(686mA / cm 2 ); Comparative Example 3: 1.8V (535mA / cm 2 ), 2.0V(935mA / cm 2 ).
[0124] Figure 5For the electrodes described in Example 2 and Comparative Example, at 1000 mA / cm 2 From the constant current polarization curves at a current density of , it can be observed that the electrode obtained in Example 2 can operate stably and efficiently for more than 500 hours without obvious performance degradation, which fully proves the excellent stability of the electrode. However, since Comparative Example 1 is not doped with Sm and Ce, the stable operation time is less than 100 hours; the stability of the electrode is: Example 2> Comparative Example 2> Comparative Example 3> Comparative Example 1. Figure 5 It can be seen that Sm and Ce doping can synergistically improve the stability of the electrode.
[0125] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which are all covered by the protection scope of the present invention.
Claims
1. A method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites, characterized in that: The following steps are involved: (1) oxidizing lignin sulfonate in a solution to obtain an oxidized lignin sulfonate solution; (2) Adding ammonia water to the oxidized lignin sulfonate solution to adjust the pH, and then adding metal salts in proportion, including Ru, Ce, and Sm, and mixing them well to carry out a hydrothermal reaction with the substrate carrier. The hydrothermal reaction temperature is 80-120°C and the time is 3-10 hours to obtain an electrode precursor; (3) The electrode precursor obtained in (2) is calcined at a temperature of 200-600°C for a time of 1-8 h to obtain an alkaline water electrolysis electrode with coordinated regulation of three metal sites.
2. The method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites according to claim 1, characterized in that: In step (1), lignin sulfonate is added to a mixture of water and ethanol, ultrasonically dispersed and mixed, and a small amount of hydrogen peroxide is added to oxidize the lignin sulfonate to obtain an oxidized lignin sulfonate solution.
3. The method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites according to claim 2, characterized in that: In step (1), the ratio of the added lignin sulfonate to hydrogen peroxide is 8-16 mmol:0.1-1 mL; the volume ratio of water to ethanol is (1-9):1; and the ultrasonic dispersion time is 1-10 min.
4. The method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites according to claim 2, characterized in that: The volume ratio of the ammonia water added in step (2) to the hydrogen peroxide solution added in step (1) is 0.1-1.5:0.1-1; the metal salt is RuCl3, Ce(NO3)3, Sm(NO3)3.
5. The method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites according to claim 2, characterized in that: In step (2), the molar ratio of the added RuCl3, Ce(NO3)3, and Sm(NO3)3 is (6.9~7.1): (1.9~2.1): (0.9~1.1).
6. The method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites according to claim 2, characterized in that: In step (2), mixing is performed by ultrasonic dispersion, and the ultrasonic dispersion time is 1 to 5 h.
7. The method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites according to claim 2, characterized in that: In step (2), the substrate carrier is one of nickel foam, nickel mesh, and carbon paper.
8. The method for preparing an alkaline water electrolysis electrode with coordinated regulation of three metal sites according to claim 2, characterized in that: In step (3), the calcination temperature is 300-500°C.
9. An alkaline water electrolysis electrode with coordinated regulation of three metal sites prepared by the preparation method described in any one of claims 1 to 8.
10. Application of the alkaline water electrolysis electrode with coordinated regulation of three metal sites as described in claim 9 in hydrogen production by water electrolysis.
Citation Information
Patent Citations
Rare earth Ce-doped RuO2 catalyst as well as preparation method and application thereof
CN117107252A
Ruthenium rare earth solid solution oxide electrocatalyst and preparation method thereof
CN117107277A
Lignin-based Ru / Co bimetallic in-situ N-doped carbon material as well as preparation method and application thereof
CN117230479A
Method for preparing transition metal-based electrocatalytic water decomposition anode catalytic material and application of transition metal-based electrocatalytic water decomposition anode catalytic material
CN118186400A
Porous ruthenium-based oxide, preparation method and application
CN119121288A